Sistemas hidráulicos de protección contra incendios, diseño, construcción, operación y mantenimiento (2016)
In this paper grade a study on the problems that currently exists in Colombia for the design, construction, operation and maintenance of hydraulic systems is fire protection. During the research development was established in the country there is a broad regulatory information on fire protection systems; however, although it is one of the most complete failure of South America when its applicability is evident in engineering projects in the phases of design, construction, operation and maintenance. In the first instance the regulations governing at the national level and particularly in the city of Bogota, where it became clear that although there the earthquake resistant NSR-10 regulation, which in its chapters J and K refers investigated the fire protection, and Agreement 20 of 1995, particularly for capital deficiencies in applying the concepts in design and construction of systems for fire protection are presented, leaving at the discretion of the designers and builders her implementation, without official bodies for accreditation and approval. This validates the overall objective of this study, which is focused on raising the urgent need to create an administrative unit validated as a competent authority responsible for reviewing and approving new engineering projects on the issue of public security in Colombia, complemented by training and certification of technicians and professionals in the field of engineering for fire protection.